PSXII-5 Rumen tissue histology of Nellore cattle submitted to either nutritional restriction or intake of concentrate feedstuffs prior to adaptation period. (7th December 2018) - Reis, B; Pereira, M; Rigueiro, A; Millen, D; Silvestre, A; Squizatti, M; Felizari, L; Arrigoni, M; Millen, D
Abstract: This study, conducted at São Paulo State University feedlot, Dracena campus, Brazil, was designed to evaluate the effects of either nutritional restriction or intake of concentrate feedstuffs prior to the adaptation period on rumen morphometrics of Nellore cattle. The experiment was designed as a completely randomized block, replicated 8 times (4 animals/pen), in which 96 22-mo-old yearling Nellore bulls (365.5 ± 39.2 kg) were fed in 24 pens according to the treatments: Restriction (Tifton hay fed at 1.4% BW + supplement); Control (Tifton hay fed ad libitum + supplement) and Concentrate (Tifton hay fed ad libitum + 0.5% BW of concentrate and supplement). This study lasted 144-d, divided into 2 periods: 32-d of pre-adaptation, when cattle were submitted to the treatments previously described, and 112-d of feeding high-concentrate diets, where cattle were fed same diets. At the end of pre-adaptation period, one animal per pen (n=24) was slaughtered for rumen evaluations. The remaining 72 animals were harvested after 112-d of feeding high-concentrate diets. A 1-cm 2 fragment of each rumen was collect from ventral sac. Histological measurements were performed in 4 papillae per animal using computer-aided light microscope for image analysis. No treatment or harvesting date main effect ( P >0.10) was observed for papillae width and papillae area. However, cattle consuming concentrate prior to adaptation had shorter ( P ab, Control: 3.54 a, Concentrate: 3.17 b ) than cattle on control group. A significant interaction was observed for keratinized layer thickness ( P =0.04) and mitotic index ( P =0.08), where no differences were observed prior to adaptation period, but cattle consuming concentrate during pre-adaptation period had thinner keratinized layer in µm (Restriction: 14.18 a, Control: 13.90 a, Concentrate: 12.76 b ) and greater mitotic index in % (Restriction: 7.95 b, Control: 8.23 b, Concentrate: 8.74 a ) after 144-d on feed. The feeding of concentrate prior to adaptation period impacted rumen tissue histology.